GenAI Tools for Cross-Cultural Dialogue and Meaning-Making: The Case of Indonesian English Education Students in Online Spaces - Dhaniella Rattu Intani; Della Teresia Orenzah; Fauziah Ibrayani; Feliza Kurnia; Puja Cahyantie; Putri Isabela; Putri Maisaroh Lastari; Sofiya Romadlon; Melisa Novianty; Hartini Agustiawati (Global Expert: Jurnal Bahasa dan Sastra, 2026)
In academic and social contexts, generative artificial intelligence (GenAI) tools are increasingly common and are often promoted as aids for classroom learning. However, limited research has explored how Indonesian English education students use GenAI to support cross-cultural dialogue and meaning-making in everyday online interactions beyond formal classroom settings. This study employed a qualitative approach involving eight English Education students from the University of Palembang. Using semi-structured interviews and thematic analysis, the study explored how students use GenAI tools in cross-cultural meaning-making, their perceptions of the benefits of these tools, and the challenges they encounter when using GenAI for cross-cultural communication. The findings indicate that students use GenAI to clarify messages, refine their language to sound more natural and culturally appropriate, and obtain real-time support during cross-cultural online interactions. Participants also perceived GenAI as helpful in supporting their cross-cultural communication and language development. At the same time, they reported challenges including inaccurate or culturally insensitive outputs, increased dependence on the tool, and unintended changes in tone that sometimes led to misunderstandings. Keywords: Cross-cultural communication, meaning-making, Generative Artificial Intelligence (GenAI), Indonesian EFL students, intercultural dialogue